The Relationship Between Solar Wind Dynamic Pressure Pulses and Solar Wind Turbulence - Ruan, Mengsi; Zuo, Pingbing; Zhou, Zilu; Shen, Zhenning; Wang, Yi; Feng, Xueshang; Jiang, Chaowei; Xu, Xiaojun; Wei, Jiayun; Xiong, Yanyan; Wang, Ludi (Frontiers in Physics, 2021)
Solar wind dynamic pressure pluses (DPPs) are small-scale plasma structures with abrupt and large-amplitude plasma dynamic pressure changes on timescales of seconds to several minutes. Overwhelming major DPP events (around 79.13%) reside in large-scale solar wind transients, i.e., coronal mass ejections, stream interaction regions, and complex ejecta. In this study, the intermittency, which is a typical feature of solar wind turbulence, is determined and compared during the time intervals in the undisturbed solar wind and in large-scale solar wind transients with clustered DPP events, respectively, as well as in the undisturbed solar wind without DPPs. The probability distribution functions (PDFs) of the fluctuations of proton density increments normalized to the standard deviation at different time lags in the three types of distinct regions are calculated. The PDFs in the undisturbed solar wind without DPPs are near-Gaussian distributions. However, the PDFs in the solar wind with clustered DPPs are obviously non-Gaussian distributions, and the intermittency is much stronger in the large-scale solar wind transients than that in the undisturbed solar wind. The major components of the DPPs are tangential discontinuities (TDs) and rotational discontinuities (RDs), which are suggested to be formed by compressive magnetohydrodynamic (MHD) turbulence. There are far more TDs than RDs both in the undisturbed solar wind and large-scale solar wind transients. The results imply that the formation of solar wind DPPs could be associated with solar wind turbulence, and much stronger intermittency may be responsible for the high occurrence rate of DPPs in the large-scale solar wind transients.